Sosialisasi Pemasangan Rangkaian Instalasi Penerangan Listrik - Ahmad Yanie; Indra Roza; E Erwin (Jurnal TUNAS, 2020)
Knowledge transfer, or better known as knowledge sharing, is the most important thing in the world of education. Not a few sources are used as learning references, ranging from printed books, ebooks, journals and various other sources. In addition to references, media or containers in the process of exchanging knowledge are always a hot topic to be discussed. This can be seen from the competition in the world of education in building a portal or academic information system that will be used as a medium that can be accessed by students anytime and anywhere, to support the smooth learning process. Also, like the Electrical Lighting Installation Technique, the development is very fast with a variety of methods and ways. In books, many tell about Electrical Lighting Installation Techniques, also on the internet and on YouTube. But it doesn't explain system-specific how it works. With the holding of PkM, the socialization of the installation of a series of electrical lighting installations is expected to help the community/students understand it